Complex archaea that bridge the gap between prokaryotes and eukaryotes - Spang, Anja; Saw, Jimmy H.; Jørgensen, Steffen L.; Zaremba-Niedzwiedzka, Katarzyna; Martijn, Joran; Lind, Anders E.; van Eijk, Roel; Schleper, Christa; Guy, Lionel; Ettema, Thijs J. G. (Nature (London), 2015)
The origin of the eukaryotic cell remains one of the most contentious puzzles in modern biology. Recent studies have provided support for the emergence of the eukaryotic host cell from within the archaeal domain of life, but the identity and nature of the putative archaeal ancestor remain a subject of debate. Here we describe the discovery of ‘Lokiarchaeota’, a novel candidate archaeal phylum, which forms a monophyletic group with eukaryotes in phylogenomic analyses, and whose genomes encode an expanded repertoire of eukaryotic signature proteins that are suggestive of sophisticated membrane remodelling capabilities. Our results provide strong support for hypotheses in which the eukaryotic host evolved from a bona fide archaeon, and demonstrate that many components that underpin eukaryote-specific features were already present in that ancestor. This provided the host with a rich genomic ‘starter-kit’ to support the increase in the cellular and genomic complexity that is characteristic of eukaryotes. This study identifies a clade of archaea that is the immediate sister group of eukaryotes in phylogenetic analyses, and that also has a repertoire of proteins otherwise characteristic of eukaryotes—proteins that would have provided the first eukaryotes with a ‘starter kit’ for the genomic and cellular complexity characteristic of the eukaryotic cell. Archaea with eukaryotic tendencies Eukaryotic cells are so very different from prokaryotes that understanding eukaryote origins and ancestry has been a puzzle. Genetic work places archaea closer than bacteria to eukaryotes, but biochemically and morphologically, archaea are closer to bacteria than to eukaryotes. But now Thijs Ettema and colleagues have identified archaea — from a core sample from the Loki's Castle hydrothermal active venting site — that fit the bill as a genomic 'starter-kit' to support the increase in the cellular and genomic complexity that is characteristic of eukaryotes. This novel archaeal group, named Lokiarchaeota, is an immediate sister group of eukaryotes in phylogenetic analyses and has a repertoire of proteins otherwise characteristic of eukaryotes.